Penerapan Lubang Resapan Biopori di Kawasan Pemukiman Kecamatan Kanigoro sebagai Pengendali Limpasan Air Hujan - Sholikah, Wahyu Niyati; Widodo, Trisno; Atmajayani, Risma Dwi (Journal of Science Nusantara, 2024)
Increasing population density has an impact on the area of ​​open green land which is reduced because it is converted into residential land. According to the 2019 land use map, the residential area is 1764 ha, but this will increase to 1867 ha in 2023. This causes the rainwater catchment area to decrease, so that rainwater flows directly into the river. Research that applies quantitative techniques is research that adheres to scientific standards that can be measured, rational, empirical, objective and methodical. The discharge calculation shows that the area with the highest flow discharge is Sawentar Village, namely 100.96 m3/s. The area that has the smallest runoff discharge is Kuningan Village, namely 19.95 m3/s. The area with the highest number of biopores in Kanigoro District is the Sawentar Village area, namely 33,405 biopores. Sawentar Village is the highest area capable of accommodating the volume of runoff based on the number of biopores, namely 209.78 m3